Formulation, Optimization, and Evaluation of Floating Alginate Beads for Sustained Drug Delivery - Prakash, Uday; Sharma, Vikas; Kumar, Yogendra; kirar, Govind; Sahu, Rohit (Journal of Neonatal Surgery, 2025)
This study focuses on the development and evaluation of floating alginate beads designed for sustained drug delivery. Beads were formulated using ionotropic gelation with sodium alginate, oil, and calcium chloride as key components. The impact of formulation variables on bead size, entrapment efficiency (EE), floating behavior, swelling index, and drug release was systematically investigated. Design-Expert® software was employed for optimization, and the best formulation (F3) demonstrated desirable properties including high EE, rapid floatation, sustained buoyancy, and controlled drug release. The optimized beads followed the Korsmeyer-Peppas release model, indicating non-Fickian transport, and exhibited excellent stability under ICH conditions